Legal Distribution of Inheritance Rights to Children Out of Marriage According to the Civil Code and the Compilation of Islamic Law - Thoyyib Izzi AlFathin; Sadari; A.H. Bahruddin (Al-Arfa: Journal of Sharia, Islamic Economics and Law, 2023)
This research is motivated by Article 171 KHI and Article 832 of the Civil Code concerning inheritance groups, it is explained in these articles that people or families who are entitled to receive inheritance include 15 groups of men and 10 groups of women, which groups are the closest people to the heir. According to Islamic law, a child out of wedlock, whether a child of adultery or li'an, is not entitled to inherit from his father's lineage and vice versa if the child out of wedlock dies, then the father cannot inherit from the child. However, when viewed from a humanitarian point of view, he can still receive inheritance from his father, but not by dividing the inheritance of children in general, but by grants, and the share may not be more than 1/3 of the inheritance. Meanwhile, according to civil law, a child out of wedlock gets a share of his father's inheritance as much as 1/3, ½, and ¾ of the share of a legitimate child depending on what class of heirs the child lives together after the heir dies. As for the source of Islamic inheritance law which is used as a guideline in the distribution of inheritance, it is listed in the Qur'an in the letter An Nisaa verses 7, 11, 12 and 176, and in the letter An Naml verse 16. Meanwhile, civil inheritance law is regulated in book II concerning objects (Van Zaken) which contains object law (Zaken Recht) and inheritance law (Erfrecht).